The Legal Subjectivity of the Iraqi State Council’s Fatwa in Disputes of a Financial Nature - Hamza, Marwa; Almayahi, Ammar (Journal of Legal Sciences, 2023)
The state council has gone through many development an stages in view of disputes in all its forms.Whether of a financial nature or of an administrative nature it is within the jurisdiction of the ordinary judiciary to a specialty jurisdiction between the ordinary and administrative then to a general and comprehensive jurisdiction to the judiciary and to get to the corridors of this facts.And to stop on the jurisdiction of the state council in settling disputes of a financial nature it should be determine what those conflicts are by defining it and then defining what falls within its competence of the state council or otherwise settled.